2016
DOI: 10.1175/jcli-d-15-0515.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Preconditioning of the Minimum September Sea-Ice Extent

Abstract: There has been an increased interest in seasonal forecasting of the Arctic sea ice extent in recent years, in particular the minimum sea ice extent. Here, a dynamical mechanism, based on winter preconditioning, is found to explain a significant fraction of the variance in the anomaly of the September sea ice extent from the long-term linear trend. To this end, a Lagrangian trajectory model is used to backtrack the September sea ice edge to any time during the previous winter and quantify the amount of sea ice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 47 publications
10
76
0
Order By: Relevance
“…Our results confirm their findings for the last 2 decades, but we also find a more moderate link for the entire 80-year period. For the recent 10 years (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014), when our ice export values are directly observed by SAR the detrended anticorrelation is r FS ice export-Sept SIE = −0.74 (Table 1), similar to Williams et al (2016). For the last 20 years we get a more modest influence (r = −0.47), and for the entire 80-year period we get r = −0.43 (Table 1).…”
Section: Consequences Of Spring Fram Strait Ice Export Anomaliessupporting
confidence: 68%
See 4 more Smart Citations
“…Our results confirm their findings for the last 2 decades, but we also find a more moderate link for the entire 80-year period. For the recent 10 years (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014), when our ice export values are directly observed by SAR the detrended anticorrelation is r FS ice export-Sept SIE = −0.74 (Table 1), similar to Williams et al (2016). For the last 20 years we get a more modest influence (r = −0.47), and for the entire 80-year period we get r = −0.43 (Table 1).…”
Section: Consequences Of Spring Fram Strait Ice Export Anomaliessupporting
confidence: 68%
“…This study suggested that Fram Strait ice area export is a good predictor for the September sea ice extent because it represents the sum of ice export from the peripheral seas and the net pack ice divergence. This study expands on the work by Williams et al (2016) by estimating the FS ice area export over a much longer time period, from 1935 to 2014. In this study, we evaluate the long-term mean, variability, and trends over this 80-year record and further examine the influence of the long-term FS export on a new time series of September SIE, also covering the years 1935-2014 (Walsh et al, 2015).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations